Selfie Photos Area and Its Implication to Water Availability and Social Culture in Wanagiri Village, Bali Indonesia - Adhika, Made (International Journal of Psychosocial Rehabilitation, 2020)
In the last few years, the village of Wanagiri has become crowded due to place of selfie in the high areas in the background of Lake Buyan. However, the area is a conservation zone that should be protected. This paper aims to discuss what are the implications of selfie photos areato the protection of water availability for Badung, Tabanan, and Buleleng Regency and socio culture in Wanagiri Villages. By direct observation and using the qualitative analysis method, it is expected that the implications can be described in the three districts. The results show that selfies in protected areas can disrupt the availability of water and socio-cultural communities.